Phytochemical profile, antioxidant and antibacterial activities of methanolic extract of Peperomia pellucida leaves revealed by GC-MS and molecular docking - SUBAKIR SALNUS; ABDUL WAHID WAHAB; MUHARRAM MUHARRAM; RUGAIYAH ANDI ARFAH; SYAHRUDDIN KASIM; ARINI RAJAB; ABDUR RAHMAN ARIF; ZULFIAN ARMAH; RIZAL IRFANDI; MUHAMMAD NUR ALAM; M. YASSER (Society for Indonesian Biodiversity, 2026)
Abstract. Salnus S, Wahab AW, Muharram, Arfah RA, Kasim S, Rajab A, Arif AR, Armah Z, Irfandi R, Alam MN, Yasser M. 2026. Phytochemical profile, antioxidant and antibacterial activities of methanolic extract of Peperomia pellucida leaves revealed by GC-MS and molecular docking. Biodiversitas 27 (2): d270219. https://doi.org/10.13057/biodiv/d270219. A comprehensive analysis of the methanol extract of Peperomia pellucida leaves was conducted using various analytical techniques, revealing a complex profile of bioactive compounds with potential therapeutic applications. Gas Chromatography-Mass Spectrometry (GC-MS) analysis identified 43 bioactive compounds within the extract, with sesquiterpenoids emerging as the predominant class of compounds. The major components identified were dillapiole (41.77%), N,N'-diacridin-9-yl-hydrazine (7.44%), and caryophyllene (6.94%), highlighting the diverse chemical composition of the extract. This extract demonstrated significant antibacterial activity against several bacterial strains, indicating its potential as a natural antimicrobial agent. Notably, it exhibited moderate effects against Klebsiella pneumoniae. The largest inhibition zone was observed against Staphylococcus aureus (14 mm), followed by Salmonella typhi (12 mm), Shigella sp. (12 mm), and Escherichia coli (11 mm). The smallest inhibition zone was recorded for K. pneumoniae (10 mm), indicating a moderate susceptibility, suggesting its possible application in treating infections caused by this pathogen. Furthermore, the extract showed remarkable antioxidant activity with an IC50 value of 4.30 µg/mL, underscoring its potential as a natural source of antioxidants. Molecular docking analysis provided insights into the mechanism of action of the components of the extract. Dillapiole, the most abundant compound (41.77%), displayed a strong binding affinity (-70.53 kJ/mol) for S. aureus proteins, suggesting its potential as a lead compound for developing novel antibacterial agents, particularly against S. aureus infections. Fourier-Transform Infrared (FT-IR) spectroscopy confirmed the presence of polyphenolic functional groups in the extract, further supporting its antioxidant properties. Overall, these results demonstrate that P. pellucida possesses potent antimicrobial and antioxidant activities linked to its diverse phytochemical composition. These findings highlight P. pellucida as a promising source of natural antioxidants and antimicrobials that support biodiversity-based drug discovery and underscore the importance of conserving medicinal plant resources for future therapeutic development.